Brazilian Valuation of EQ-5D-3L Health States: Results from a Saturation Study. (February 2016) - Santos, Marisa; Cintra, Monica A. C. T.; Monteiro, Andrea L.; Santos, Braulio; Gusmão-filho, Fernando; Andrade, Mônica Viegas; Noronha, Kenya; Cruz, Luciane N.; Camey, Suzi; Tura, Bernardo; Kind, Paul
Background. Most EQ-5D-3L valuation studies include the same sample of health states that was used in the protocol of the original UK Measurement and Valuation of Health (MVH) study. Thus far, no studies using a time tradeoff utility elicitation method have been carried out using all 243 EQ-5D health states. Because the values and preferences regarding health outcomes differ among countries, it is essential to have country-specific data to enable local high-level decisions regarding resource allocation. This study developed a country-specific set of values for EQ-5D-3L health states.Methods. A multicentric study was conducted in 4 Brazilian areas. A probabilistic sample of the general population, aged 18 to 64 y, stratified by age and gender, was surveyed. The interview followed a revised version of the MVH protocol, in which all 243 health states were valued. Each respondent ranked and valued 7 health states using the TTO in a home interview.Results. Data were collected from 9148 subjects. The best-fitting regression model was an individual-level mixed-effects model without any interaction terms. The dimensions "Mobility" and "Usual Activities" were associated with higher losses in health state utility value. The "Anxiety/Depression" dimension was the domain that contributed to lower losses in health state utility value.Conclusions. This study generated significant insight into the Brazilian population's health preferences that can be applied to health technology assessment and economic analyses in Brazil. This information represents an important new tool that can be used in Brazilian health policy creation and evaluation.